Strategi Komunikasi Jurnalis Perempuan Dalam Peliputan Kasus Kekerasan Seksual Terhadap Perempuan Di Kota Padang - Rahmadani, Rina; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The term sexual violence is not a new term in Indonesia because this type of violence occurs almost every year in the country. News about this issue demands social empathy. Therefore, journalists need to be careful in investigating sexual violence cases because journalism ethics need to be applicable in digging up information and collecting news to be analyzed and to be reported to the public. The purpose of this research is to find out how female journalists applied communication strategies in investigating sexual violence cases towards women. This research uses a qualitative approach, in the form of a case study, and its data collection techniques are in-depth interview, observation, and documentation. Data analysis techniques are data reduction, data display, and conclusion remarks. The theory used in data analysis was the Social Penetration Theory. This theory refers to interpersonal relationships. According to Irwin Altman and Dalmas Taylor, social penetration theory illustrates the process of relationship ties between individuals that move from a superficial level of communication to the most complex level of communication. The result of this research explains that the communication strategy of female journalists in investigating sexual violence towards women is related to the application of feeling empathy, listening attentively, being open to knowing different views, and holding an even better relationship with the person being investigated for the news.